2004
DOI: 10.1529/biophysj.103.034280
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Short-Chain Alcohols on Interfacial Tension, Mechanical Properties, Area/Molecule, and Permeability of Fluid Lipid Bilayers

Abstract: We used micropipette aspiration to directly measure the area compressibility modulus, bending modulus, lysis tension, lysis strain, and area expansion of fluid phase 1-stearoyl, 2-oleoyl phosphatidylcholine (SOPC) lipid bilayers exposed to aqueous solutions of short-chain alcohols at alcohol concentrations ranging from 0.1 to 9.8 M. The order of effectiveness in decreasing mechanical properties and increasing area per molecule was butanol>propanol>ethanol>methanol, although the lysis strain was invariant to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
298
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 281 publications
(340 citation statements)
references
References 86 publications
(108 reference statements)
39
298
1
2
Order By: Relevance
“…It is well known that alcohol chain length is directly correlated with its bilayer modifying potency (3,62,63). We hypothesized that if the observed effects on vesicle fusion from ethanol were the result of changing of some membrane properties, then changing alcohol chain length may influence the magnitude of the excitation and inhibition of fusion that we observe.…”
Section: Cis Addition Of Alcoholsmentioning
confidence: 78%
See 2 more Smart Citations
“…It is well known that alcohol chain length is directly correlated with its bilayer modifying potency (3,62,63). We hypothesized that if the observed effects on vesicle fusion from ethanol were the result of changing of some membrane properties, then changing alcohol chain length may influence the magnitude of the excitation and inhibition of fusion that we observe.…”
Section: Cis Addition Of Alcoholsmentioning
confidence: 78%
“…The increase in surface area will decreases hydration pressure (76). This suggests a plausible mechanism for the action of alcohol in increasing fusion as it has been shown that alcohol increases surface area per head group (63).…”
Section: Possible Mechanisms For Enhancement Of Fusion By Cis Additiomentioning
confidence: 94%
See 1 more Smart Citation
“…Lipid bilayers obey Traube's rule of interfacial tension reduction for short chain alcohols (methanol-butanol), i.e., for every additional CH 2 group, an alcohol becomes three times more effective in decreasing the interfacial tension of the bilayer [77]. Therefore, the alcohol partitioning into the bilayer-water interface are responsible for the Traube's rule dependence, and hence for every additional CH 2 group, three times more alcohol partitions into the interface.…”
Section: Effect On the Phase Behaviourmentioning
confidence: 99%
“…The concentration dependence of the partitioning of short chain alcohols (methanol to butanol) into the bilayer-water interface was also explored by Ly and Longo who related this effect to lowering of interfacial tension by alcohol molecules, which follows Traube's rule [77]. For each CH 2 group in an alcohol, a three times lower alcohol concentration is required to reach the same interfacial tension.…”
Section: Partitioning Equilibrium At the Water/surfactant Interfacementioning
confidence: 99%